Understanding Criminology in the Modern World: An Exploration of Modern Trends and Applications - Kalimullah, Mohd; Khanday, Sumbl Ahmad; Rizvi, Afreen (International Journal of Criminology and Sociology, 2026)
Criminology has evolved considerably from its classical and positivist foundations to address the complexities of contemporary society. This paper examines the transformation of criminological thought, highlighting the shift from traditional explanations of crime toward interdisciplinary approaches that incorporate technological, social, environmental, and cultural dimensions. Particular attention is given to emerging fields such as cybercrime studies, bio-criminology, feminist criminology, and green criminology, which broaden the scope of conventional criminological inquiry. The study analyses how globalization, digital technologies, and changing social structures have reshaped patterns of criminal behavior and challenged existing theoretical frameworks. It further explores the implications of these developments for crime prevention, criminal justice policy, and future criminological research. By synthesizing contemporary perspectives, the paper argues that criminology must continuously adapt to emerging forms of crime and evolving societal conditions. The analysis contributes to ongoing debates on the relevance of modern criminological theories in understanding and responding to twenty-first-century criminality.